1976
DOI: 10.1002/1097-0142(197608)38:2<740::aid-cncr2820380217>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of lymphocytes from primary neoplasms of lymphoid tissues

Abstract: Proliferative responses by blood and tumor lymphocytes to plant mitogens and allogeneic leukocyte antigens were tested concomitantly on 12 patients with Hodgkin's disease, 10 with chronic lymphocytic leukemia, and seven with non-Hodgkin's lymphomas. In 13 control studies, 3H-thymidine incorporation by blood and lymph node lymphocytes was brisk and, overall, comparable. With Hodgkin's disease, where extent of disease involvement and lymphocyte-depleted tumor histology were factors in the degree of responsivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These disorders include chronic mucocutaneous candidiasis (11,17), solid tumors (18,19), primary tumors of lymphoid tissues (20,21), and systemic lupus erythematosus (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These disorders include chronic mucocutaneous candidiasis (11,17), solid tumors (18,19), primary tumors of lymphoid tissues (20,21), and systemic lupus erythematosus (22).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired lymphoproliferative responsiveness occurs frequently with various immunodeficiencies (21,(24)(25)(26). Abnormal plasmas with a type IV or V lipoprotein pattern may interfere with other immune responses as well, particularly those that involve lymphocyte proliferation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients with tumour-engaged spleens an inverse relationship between spleen size and the lymphocyte response to PWM stimulation has been reported . Moreover, mitogen-reactive lymphocytes are also present in the spleen in patients with severe blood-lymphocyte defects (Twomey et al, 1976;Willson et al, 1977). Imbalance in regulation by macrophages or T cells may also contribute (Twomey et al, 1975;Goodwin et al, 1977) but has not been confirmed .…”
Section: Statisticsmentioning
confidence: 99%
“…The proliferative response to anti-gens (5,6) and mitogens (3,7), especially at suboptimal mitogen concentrations (8), is often impairedl. Protein synthesis (9), mediator production (10), and cytotoxicity (11) by cultured lymphocytes are often subniormiial.…”
Section: Introductionmentioning
confidence: 99%